Political Capitalism vs the Public Interest: Influence in the Presence of Checks and Balances - Stergios Skaperdas; Samarth Vaidya (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We examine how political capitalism can develop within modern states that typically have many types of checks and balances. We first discuss how this can occur through various influence channels: government executive and regulatory agencies, legislators, litigation, the press, and the public sphere more generally. We then develop a model in which a group representing the public interest competes for policy implementation with a group that seeks private advantage. A non-venal decision maker makes the policy decision based on the lobbying of the two groups, which is partly restrained by an existing, status-quo policy and by the decision maker's expertise. Because of free-rider problems but also because of a greater ability to develop a lobbying infrastructure, the group seeking private advantage has a better chance of implementing its policy even when the status quo policy is aligned with the public interest. Only when the decision maker has a high enough level of expertise and favorable status quo policy does the public interest group have a better chance of winning.
Keywords: D72; D73; H11; P10; 330; political capitalism; lobbying; rent-seeking; checks and balances; persuasion; political influence